(untitled) (Revista Apotheke, 2024)
The text presents the initial results of an exercise to dismantle the relationship between art, education and teacher training in the visual arts. This methodological attitude takes as its principle the investigative approaches known as post-critical. When working on the disengagement of the knowledge that constitutes art teaching in the context of basic education, I came across a theme that has been left out of our discussions: practice. Without trying to point out a path to be followed, I’m interested in presenting the questions that have been raised on the subject, while at the same time pointing out ways that can offer us clues to recovering a possible poetic dimension to art teaching at school, less technical and more inventive, less instrumentalizing and more open to experimentation. At the end of the text, questions are presented that seek to broaden this debate interested in understanding the place of practice in art teaching.